Culprit-only versus immediate multi-vessel revascularization in patients with AMI complicated by advanced cardiogenic shock undergoing VA-ECMO. (3rd May 2023) - Choi, K H; Yang, J H; Park, T K; Lee, J M; Song, Y B; Hahn, J Y; Choi, S H; Ahn, C M; Yu, C W; Gwon, H C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This study was supported by unrestricted grants from the Korean Society of Interventional Cardiology. Aims: Despite the benefit of culprit-only percutaneous coronary intervention (PCI) in the CULPRIT-SHOCK trial, the optimal revascularization strategy for a refractory cardiogenic shock (CS) requiring mechanical circulatory support devices remains controversial. This study aimed to compare clinical outcomes between the culprit-only and immediate multi-vessel PCI strategies in patients with acute myocardial infarction (AMI) complicated by CS who underwent venoarterial-extracorporeal membrane oxygenation (VA-ECMO). Methods and Results: This study was patient-pooled data from the RESCUE and SMC-ECMO registries. A total of 408 AMI patients with multi-vessel disease who underwent VA-ECMO due to refractory CS were included in this analysis. The study population was classified into culprit-only versus immediate multi-vessel PCI according to non-culprit lesion (NCL) treatment strategies. The co-primary endpoints were 30-day mortality or renal-replacement therapy and 12-month follow-up mortality. Among the study population, 241 (59.1%) underwent culprit-only PCI and 167 (40.9%) underwent immediate multi-vessel PCI. Compared with culprit-only PCI, immediate multi-vessel PCI was associated with significantly lower risks of 30-day mortality or renal-replacement therapy (66.8% vs. 54.5%, p=0.02) and all-cause mortality during 12 months of follow-up (59.5% vs. 47.8%, hazard ratio [HR] 0.70; 95% confidence interval [CI] 0.53–0.92, p=0.01) in patients with AMI and CS who underwent VA-ECMO. These results were also consistent in the 290 pairs of propensity score-matched population (55.6% vs. 46.1%, HR 0.71; 95% CI 0.51–0.98, p=0.04). Conclusion: Among AMI patients with multi-vessel disease complicated by advanced CS, immediate multi-vessel PCI might be associated with improved clinical outcomes in those undergoing VA-ECMO. Summarizing Illustration Outcomes According to Treatment Strategy